1981
DOI: 10.1002/1098-108x(198123)1:1<70::aid-eat2260010107>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Rumination in infancy: Recent behavioral approaches

Abstract: The published literature on behavioral treatments of rumination is reviewed, and new case material on two recently reported procedures is presented. Rumination, a medical condition of infancy involving repeated regurgitation of previously ingested food, has historically been treated from a psychodynamic approach involving extended in‐patient treatment by mother surrogates. This procedure is both time‐consuming and very costly. The initial behavioral approach involved electric shock. Single‐case studies reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Another study found that the mothers of ruminating infants tended to have high degrees of depression and an impaired coping style, characterized by high degrees of dependency and immaturity [12]. However, other investigators have suggested that infant rumination is actually a learned behavior, in which infants who received attention in response to episodes of rumination were more likely to repeat it and that "extinguishing" the rumination behavior with negative reinforcement (ie, aversive stimuli or withdrawing attention) may be an effective treatment strategy [13].…”
Section: Infant Rumination Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that the mothers of ruminating infants tended to have high degrees of depression and an impaired coping style, characterized by high degrees of dependency and immaturity [12]. However, other investigators have suggested that infant rumination is actually a learned behavior, in which infants who received attention in response to episodes of rumination were more likely to repeat it and that "extinguishing" the rumination behavior with negative reinforcement (ie, aversive stimuli or withdrawing attention) may be an effective treatment strategy [13].…”
Section: Infant Rumination Syndromementioning
confidence: 99%
“…Operant conditioning has been shown to be helpful in treating infants or severely developmentally disabled children with rumination [13,24]. The selective withdrawal of attention in response to rumination and the application of additional attention in response to appropriate feeding behavior have been used effectively by a number of clinicians.…”
Section: Operant Conditioningmentioning
confidence: 99%
“…In some subjects it was directly imitative, â€oe¿ a learned habit― (Levine et a!, 1983);in others, particularly infants and the mentally defective, securing attention, either as care or disapproval, acted as a reinforcer, which required countering by a consistent programme of social rewards and punishments (Chatoor eta!, 1984). Most controversial were aversive techniques, such as electric shock, first used with older, mentally retarded subjects in 1968, and with infants in 1969 (Lavigne et a!, 1981) and the application of unpleasant substances to the tongue (e.g. lemon juice, tabasco sauce).…”
Section: Other Approachesmentioning
confidence: 99%
“…The teenage male described by Vos (1830) was entirely fit; Effiotson (1835) referredto an octo genarianruminatorin perfect health, and Bourneville and Séglas (1883) confirmed that merycism could occur in completely healthy individuals. Runge (1895) described a ruminating father and son who were strong and well; Osler (1912) asserted that â€oe¿ the habit does not necessarily impair the health―.More recently, Lavigne et a! (1981) warned against the assumption of psychopathology in ruminators and their families and Levine eta!…”
Section: Other Approachesmentioning
confidence: 99%
See 1 more Smart Citation